Analisis Kualitas Butir Soal Ujian Akhir Semester Genap Mata Pelajaran Simulasi dan Komunikasi Digital Kelas X Multi Media di S/mk Negeri 4 Kendari Tahun Ajaran 2021/2022 - Anazar; Muhammad Munir (Journal of Information Technology and Education (JITED), 2024)
Abstract This research was conducted with the aim of knowing the quality of the Second Semester Final Examination questions items in the Class X Multi Media Digital Simulation and Communication subject at SMK Negeri 4 Kendari in the academic year 2021/2022 which was observed based on the aspects of validity, reliability, differentiation, difficulty level, and the effectiveness of the distractor. This research was descriptive research with a quantitative approach. The subjects in this research were 69 students in class X Multi Media at SMK Negeri 4 Kendari who took the Second Semester Final Examination, with details of 33 students in Class MM.A and 36 students in Class MM.B. The object of this research was the Second Semester Final Exam questions in the Class X Multi Media Digital Simulation and Communication subject at SMK Negeri 4 Kendari in the academic year 2021/2022. The data collection technique used in this research was the documentation technique. The research data analysis technique was carried out by inputting all the students’ answer options on the question answer sheets along with the answer keys into the ANATES V4.09 application. The results of the research that had been done showed: 8 items (27%) had very good quality, 12 items (40%) had good quality, 8 items (27%) had fairly good quality, 1 item (3%) had bad quality, and 1 item (3%) had very bad quality.